Ambiguity, ambiguity aversion and stores of value: The case of Argentina - Eduardo Ariel Corso (Cogent Economics & Finance, 2014)
We study the household portfolio allocation in an economy with a history of nominal anchor volatility. Applying smooth ambiguity preferences to a static portfolio choice problem, we rationalize two facts about the Argentine experience of the last 20 years: the dollarization of household financial assets and its bias towards investment real estate as a means of preserving the real value of wealth. We find that ambiguity explains portfolio dollarization. In addition, ambiguity aversion reduces the demand for assets denominated in US dollars and increases the demand for investment real estate.
Keywords: G10; G11; D1; 330; ambiguity; ambiguity aversion; Argentina; dollarization; investment real estate; stores of value